The Relationship between Information Resource and Infectious diseases conception - Chou, Pin-Fenn; Wang, Ying-Chun (IJRDO - Journal of Business Management, 2016)
Excepting for some factors such as the terrorism and political instability will affect to passengers’ tourist intention (Sonmez and Graefe, 1998). Recent year, to bring many diseases to infectious are belong to transnational behavior from tourism, which are also affects travelers to choose visit location for their tours. The method of this study, the Investigation is used to the questionnaire to interview the students. And the analysis methods including reliability analysis, validity analysis, path analysis. The results found that the respondents perception had a positively and significantly the relationship which between information resource and knowledge for the infect diseases. The results can provide the reference for prevent the infect diseases.